Pengaruh Kualitas E-Service dan Nilai Pelanggan terhadap Kepuasan Pelanggan Tokopedia di Kota Batam - Essa, Devyd Irfan; Evyanto, Winda (J-MAS (Jurnal Manajemen dan Sains), 2024)
The aim of this research is to see how customer value and e-serial quality influence Tokopedia customer satisfaction in Batam City. The population of Tokopedia users or consumers in 2024 is the subject of this research. By using purposive sampling and the Lameshow formula approach, 100 respondents were selected as samples for this research. Multiple linear regression was used for data analysis, along with classic influence, hypothesis and assumption testing, as well as data quality testing. The results of multiple linear regression analysis show that there is a relationship of 18.8% between electronic service quality and customer happiness. Customer satisfaction is influenced by customer value by 31%. Using coefficient of determination analysis (R2), the results show that customer value and e-service quality together explain 29.7% of the variation in customer satisfaction. In addition, the results of the t test and F test show that customer value and e-service quality together have a positive and significant effect on customer satisfaction at Tokopedia in Batam City.